2010
DOI: 10.1007/s11104-010-0625-6
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of ions during seed development under controlled saline conditions of two Suaeda salsa populations is related to their adaptation to saline environments

Abstract: Controlled conditions were used to investigate the relationship between ion distribution in developing seeds of two Suaeda salsa populations and seed germination and seedling emergence. Seeds were harvested from S. salsa plants that had been treated with 1 or 400 mM NaCl for 122 (saline inland population) or 135 days (intertidal zone population) in a glasshouse. Germination and seedling emergence were evaluated under salinity. In both populations, more ions were accumulated in the pericarps of plants cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The intertidal population is usually submerged completely in seawater during its whole life cycle, and the salt concentrations in the soil are always higher than the inland population (Liu 2006;Song et al 2009b). The present results support the previous suggestions referred by Li et al (2011), i.e. the intertidal population should accumulate a minimal level of ions in embryos to ensure seedling establishment in highly saline environments.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The intertidal population is usually submerged completely in seawater during its whole life cycle, and the salt concentrations in the soil are always higher than the inland population (Liu 2006;Song et al 2009b). The present results support the previous suggestions referred by Li et al (2011), i.e. the intertidal population should accumulate a minimal level of ions in embryos to ensure seedling establishment in highly saline environments.…”
Section: Discussionsupporting
confidence: 92%
“…Means in each column that have different letters are significantly different at P 5 0.05; data are means+SE, n ¼ 4. intertidal population than in the inland population when plants were cultured in 400 mM NaCl. Correspondingly, seedling emergence at 600 mM NaCl was lower with seeds from the intertidal population than with seeds from the inland population (Li et al 2011). They suggested that plants of the intertidal population required a minimal level of ions in embryos to ensure seedling establishment in highly saline environments (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…salsa), a C 3 plant distributed in saline soil areas of northern China, has been paid much attention due to its economic and ecological value in saline agriculture (Li et al 2011;Song et al 2008;Zhao et al 2002). S. salsa grows optimally in the presence of about 200 mM NaCl (Song and Wang 2014) and accumulates Na + to the concentration of about 400 mM based on the tissue water content in its leaves without injury, indicating that S. salsa is a typical salt-accumulating halophyte (Wang et al 2004(Wang et al , 2007Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%